The Effect of Cost-Volume-Profit Structure on Full and Direct Costing Net Income: A Generalized Approach. - Ricketts, Donald E.; Purdy, Charles R. (The Accounting Review, 1974)
This article focuses on the effects of cost-volume-profit structure on full and direct costing net income. The purpose of the article is to provide a framework for such comparisons. First, the authors identify several important variables which affect the percentage difference between absorption and direct costing net income. These variables include the relative mix of manufacturing versus nonmanufacturing fixed costs as well as the relative differences between production and sales volume. Second, these variables are normalized so that the impact of alternative C-V-P structures can be readily determined.